Perception of university students on the use of ChatGPT in academic writing - Loayza-Maturrano, Edward Faustino (2024)
The purpose of the study was to analyze the perceptions of university students about the use of chatGPT artificial intelligence technology in academic writing activities of essays and review articles. Methodologically, the research had a descriptive-correlational design whose sample was 63 university students, chosen by convenience and with informed consent. A questionnaire of 24 questions was applied seeking to know the perception of the characteristics of the use of chatGPT. The results allowed us to detect problems in the format of citations, verification of sources, review of responses, and educational implications were drawn. Most students perceived chatGPT positively as a tool to save time and improve the effectiveness of the writing process, and they used chatGPT more frequently to generate ideas and collect information. However, students pointed out problems with the quality, source and reliability of the information. It is concluded that training in comparison and contrast skills, synthesis and judgment of information that comes from multiple sources should be improved. Additionally, clear and specific guidelines and ethical standards for the use of chatGPT should be provided.